Educational reforms for the actualization of the rights of persons with disabilities (2014)
This paper examined the educational reforms on the rights of access to education (RtE) of persons with disabilities (PWDs) from the backdrop of the six Geo-political zones of Nigeria. It argued that the lack of a precise legislation regulating the RtE of PWDs, the non-domestication of the United Nations Convention on the Rights of Persons with Disabilities (CRPD) and non-inclusion of the RtE in the Constitution of the Federal Republic of Nigeria (CFRN) as a justiciable right have created a lacuna in the implementation of de jure and de facto equality which then hinders the protection of the RtE of PWDs. The study utilized 399 participants including tertiary Institutions’ students, teachers and administrators that responded to self- constructed and validated research measures in an ex-post-facto research design format. Statistical inference was taken at 0.05 alpha. Prominent among the findings showed that an approximate 76% of the participants submitted that PWDs do not have easy access to educational facilities; and subsequently impede their potential to learn. Furthermore, 73.0% of the participants said that educational policies and reforms for the right to and equal access to education is lopsided and adversely affect the PWDs. Finally, 69.0% also failed to affirm that educational policies and reforms have balance structures catering for both the PWDs and their counterpart (i.e. the people without disabilities). It therefore recommended that the constitutional provision on education should form part of the enforceable fundamental rights while the provision of existing laws, policies on education and other developmental plans in Nigeria should mainstream disability.